THE EFFECTIVENESS OF USING DUOLINGO TO MASTERY STUDENTS’ VOCABULARY IN ENGLISH TEACHING - Abang Intan, Alia Febrian; Kornelia Rini Sri Rahayu; Y. Gatot Sutapa. Y (Epigram, 2024)
Vocabulary is a crucial component that supports four important English language skills. Vocabulary mastery is more important than grammar. Vocabulary is an important component in the study of languages, and it is invaluable and students must master vocabulary. Mastering a helpful vocabulary facilitates more effective interaction though lacking for perfect grammatical structure. Traditional vocabulary techniques for learning, that usually involve rote learning, are sometimes boring and depressing for students. The effectiveness and motivation of the learning process are both enhanced by the use of relevant media in a learning environment. Effective use of media will enhance student learning outcomes and build innovation. The use of technology in the classroom, particularly using applications such as Duolingo, provides a modern solution for vocabulary mastery. Its fun and interactive way to study vocabulary is offered by the free online language learning tool Duolingo. Students found the platform appealing because of its game-like functions, like rankings and competitions. Furthermore, Duolingo has an element called "Duolingo for Schools" that enables teachers to monitor and interact with students' progress. The purpose of this research is to evaluate the way students will master English vocabulary with the use of the Duolingo application. Using the utilization of Duolingo's practicality, convenience, and comprehensiveness, students can effectively and fun to master their vocabulary. The use of technological advances in language learning goes hand in hand with the increasing reliance on mobile devices in contemporary education.